2019
DOI: 10.12998/wjcc.v7.i19.3126
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma of soft tissue in pleural cavity: A case report

Abstract: BACKGROUNDClear cell sarcoma (CCS) of soft tissue is a rare malignant soft tissue sarcoma usually reported to locate at distal end of extremities and rarely at trunk. Herein, we report a case of CCS in pleural cavity.CASE SUMMARYA 31-year-old male was admitted for an uncertain mass in left pleural cavity in routine physical examination without any symptoms. A VATS surgery was performed to remove the tumor. The pathological finding displayed a cystic mass with 6.5 cm at the longest diameter, dark red in section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…CCSK is a rare renal malignancy after nephroblastoma, and its histologic and immunohistologic features are unknown [4] . In clinical presentation, the main symptoms of CCSK are abdominal masses, abdominal pain, hematuria, and other atypical symptoms, and the lack of speci city of these symptoms can lead to preoperative misdiagnosis of wilms tumor [3] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCSK is a rare renal malignancy after nephroblastoma, and its histologic and immunohistologic features are unknown [4] . In clinical presentation, the main symptoms of CCSK are abdominal masses, abdominal pain, hematuria, and other atypical symptoms, and the lack of speci city of these symptoms can lead to preoperative misdiagnosis of wilms tumor [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell sarcoma of kidney (CCSK) is a rare renal malignancy that occurs in approximately 2-5% of renal tumors in children, second only to Wilms Tumor (WT), with an age of onset of approximately 2-4 years [1,2] . The incidence of CCSK is low, but bone metastases occur frequently and its prognosis is inferior to that of WT tumors, and the brain is the most prevalent location of late recurrence in ccsk [3,4] . Due to the use of more intense chemotherapy and radiotherapy in recent years, the outcome of CCSK has greatly improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear cell sarcoma of soft tissue (CCS-ST) is a distinctive entity that has a predilection for the distal extremities of young to middle-aged adults. This rare tumor type can also arise in some unusual sites, including the head and neck region, 1,2 pleura, 3,4 trunk, 5 retroperitoneum, 6 penis, 7,8 bone, 9,10 and visceral organs. 11 In 2003, Zambrano et al 12 reported a small series of 6 gastrointestinal (GI) tumors sharing morphological features in common with CCS-ST but showing essential differences, particularly the absence of expression of melanocytic markers or ultrastructural evidence of melanocytic differentiation.…”
Section: Introductionmentioning
confidence: 99%